PENGARUH TRANSPARANSI, KOMPETENSI, DAN SISTEM AKUNTANSI KEUANGAN TERHADAP AKUNTABILITAS PENGELOLAAN KEUANGAN DAERAH DENGAN PENERAPAN SISTEM PENGENDALIAN INTERNAL PEMERINTAH SEBAGAI VARIABEL MODERASI (STUDI KASUS KANTOR WALIKOTA LANGSA) - Syahrin, Ainul Alfi; Irfan, Irfan; Januri, Januri (Worksheet : Jurnal Akuntansi, 2025)
This research aimed to investigate the effects of transparency, competence, and financial accounting systems on the accountability of regional financial management, with the Government Internal Control System (SPIP) serving as a moderating variable. The study population comprised all 78 employees of the Finance Department at the Langsa Mayor’s Office, according to internal records as of January 2025. Using a saturated sampling technique, the entire population was included as the research sample, resulting in 78 respondents. Data were collected via questionnaires that had been validated and tested for reliability. The analysis was conducted using moderation analysis with SmartPLS 4.0 to assess both the direct impact of the independent variables on the dependent variable and the moderating effect of SPIP in enhancing or diminishing these relationships. The results show that transparency has a significant positive effect on the accountability of regional financial management, indicating that an increase in transparency can enhance the realization of accountable financial practices. The competency of regional government officials also demonstrates a significant positive effect, meaning that higher competency levels contribute to improved accountability in financial management. Furthermore, the financial accounting system shows a significant positive effect, suggesting that the effectiveness of accounting procedures and systems plays an important role in supporting accountability. Regarding the moderating effect of SPIP, transparency does not exhibit a significant influence, while both competency and the financial accounting system are strengthened by SPIP in their relationship with accountability. These findings highlight that SPIP serves as an important control mechanism that enhances the role of competence and financial accounting systems in achieving accountable regional financial management.